Предмет: Алгебра,
автор: nelya417
решите, пожалуйста))))))
Приложения:
Ответы
Автор ответа:
0
√(x-1+2√(x-2))=√(x+7-6√(x-2))
Возведём обе части уравнения в квадрат:
x-1+2√(x-2)=x+7-6√(x-2)
8√(x-2)=8 I÷8
√(x-2)=1
Возведём обе части уравнения в квадрат:
x-2=1
x=3.
Проверка: 3-1+2√(3-2)=x+7-6√(3-2) 2+2*√1=3+7-6√1 4≡4
Ответ: х=3.
Возведём обе части уравнения в квадрат:
x-1+2√(x-2)=x+7-6√(x-2)
8√(x-2)=8 I÷8
√(x-2)=1
Возведём обе части уравнения в квадрат:
x-2=1
x=3.
Проверка: 3-1+2√(3-2)=x+7-6√(3-2) 2+2*√1=3+7-6√1 4≡4
Ответ: х=3.
Похожие вопросы
Предмет: Английский язык,
автор: lauradokter12
Предмет: Алгебра,
автор: usenkulovasamia
Предмет: История,
автор: velastandoff05
Предмет: Алгебра,
автор: Аноним
Предмет: Право,
автор: kisa090